Adrenal Hemorrhage in Patients with Systemic Lupus Erythematosus and Antiphospholipid Syndrome: A Case Report and Literature Review - Weiwei Jiang; Danrui Chen; Daizhi Yang; Longyi Zeng; Wen Xu; Shuo Lin (International Journal of Endocrinology)
Antiphospholipid syndrome (APS) is an autoimmune disorder while adrenal hemorrhage could be its rare complication. Herein, we report the case of a 32-year-old unmarried woman with a history of systemic lupus erythematosus (SLE) who was hospitalized after complaints of upper abdominal pain, limb weakness, and loss of appetite for 2 weeks. Laboratory examination revealed hyponatremia, low plasma cortisol levels, increased adrenocorticotropic hormone levels, and a positive anticardiolipin antibody status. Furthermore, computed tomography (CT) revealed the presence of bilateral adrenal masses. Ultimately, based on dynamic changes in CT images, these masses were diagnosed as adrenal hemorrhage owing to APS. A computer-assisted literature search was conducted to identify cases of primary adrenal insufficiency associated with APS and/or SLE. The clinical features, laboratory examination, treatments, and outcomes of these cases were summarized. Our findings emphasize the importance of screening for adrenal insufficiency in patients with SLE or APS who present with abdominal complaints, asthenia, and hyponatremia. It is also recommended to test for APS all patients with adrenal hemorrhage.